Empowering Junior High School Students` Narrative Writing Skills Through Google Site - Lucky Kurnia Wati; Anis Trisusana (Institut Agama Islam Negeri Madura, 2024)
Technology has demonstrated its potency by offering opportunities to connect individuals, communities, and society, which can be utilized to promote learning writing. This study aims to determine the use of Google Site to improve students' writing abilities through narrative text. The researcher employed a mixed-method approach by combining pre-test and post-test scores and observation in 30 students of second grade at junior high school. The result of the study showed that students' posttest scores (M=76.27) were higher compared to the pretest (M=63.77). The observation revealed that the teacher needed to prepare and develop the website before publishing it. The process of creating the site was not difficult because it has simple features that are easy to understand. Adding text, pictures, and backgrounds were the main features that often used to make it. In addition, allowing students to learn from the website and creating their own, helped them to enjoy the learning process that resulted in their writing performance.